If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.16x + 0.6(x + -4) = 0.01(2x + -1) Reorder the terms: 0.16x + 0.6(-4 + x) = 0.01(2x + -1) 0.16x + (-4 * 0.6 + x * 0.6) = 0.01(2x + -1) 0.16x + (-2.4 + 0.6x) = 0.01(2x + -1) Reorder the terms: -2.4 + 0.16x + 0.6x = 0.01(2x + -1) Combine like terms: 0.16x + 0.6x = 0.76x -2.4 + 0.76x = 0.01(2x + -1) Reorder the terms: -2.4 + 0.76x = 0.01(-1 + 2x) -2.4 + 0.76x = (-1 * 0.01 + 2x * 0.01) -2.4 + 0.76x = (-0.01 + 0.02x) Solving -2.4 + 0.76x = -0.01 + 0.02x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.02x' to each side of the equation. -2.4 + 0.76x + -0.02x = -0.01 + 0.02x + -0.02x Combine like terms: 0.76x + -0.02x = 0.74x -2.4 + 0.74x = -0.01 + 0.02x + -0.02x Combine like terms: 0.02x + -0.02x = 0.00 -2.4 + 0.74x = -0.01 + 0.00 -2.4 + 0.74x = -0.01 Add '2.4' to each side of the equation. -2.4 + 2.4 + 0.74x = -0.01 + 2.4 Combine like terms: -2.4 + 2.4 = 0.0 0.0 + 0.74x = -0.01 + 2.4 0.74x = -0.01 + 2.4 Combine like terms: -0.01 + 2.4 = 2.39 0.74x = 2.39 Divide each side by '0.74'. x = 3.22972973 Simplifying x = 3.22972973
| 15-w/4=23 | | 112=7xb | | -1/2h=4 | | -3+.66x=3 | | 6y-2-4y+1=0 | | -1/10x+8=46 | | 6m+3m+6=-2m+-7 | | 12/18x+6/9=4x+2 | | 5x+12/3+120=174 | | 7y-10-4y+8=0 | | -2v+8=2 | | -.23(-.194)+.2(-.194-2)= | | -1/2x-7-11 | | x+6/3=-4 | | A+18=5a-3+a | | 11x+2/-8=-3 | | -4(2x-4)=-9*48 | | -95.66=3.5+7.4(-1.4n-3.6) | | m-8=26 | | x-5/3x+1 | | 13x+24/10-20=-15 | | 8xy+40x= | | (5-x)*(3-x)*(-6-x)+18=0 | | 18x(-5)=3(6x-2) | | 5(2x+3)=24+x | | x^3+2-4x=0 | | 11+x=66 | | 15/8x=21/4(x-3) | | 5x-6=3x-x-8 | | 0.66a-0.75=0.75a | | 25+x-6+x-6=145 | | 450/50 |